MENINGKATKAN PRODUKSI DAN PENDAPATAN USAHATANI SAWAH DI DAERAH ALIRAN SUNGAI (DAS) SERAYU MELALUI USAHA PERBAIKAN SISTEM PERTANAMAN - ANNY HARTATI (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2010)
Water problems are big problems which are not easily solved in the frame work of the increasing food production especially for rice. The solution will be easier if the government’s policy onfood diversity can be realized successfully because second crop require less water for their growth. In conclution, problems rising in increasing food production through enterprice which are more with commodity approach can be overcome by improving cropping systems.